Yeast and Human RNA Polymerase II Elongation Complexes: Evidence for Functional Differences and Postinitiation Recruitment of Factors - Pardee, Timothy S. (American Society for Microbiology, 2003)
Immobilized DNA templates, glycerol gradient centrifugation, and native gel analysis were utilized to isolate and compare functional RNA polymerase II (RNAPII) elongation complexes from Saccharomyces cerevisiae and human cell nuclear extracts. Yeast elongation complexes blocked by incorporation of 3′-O-methyl-GTP into the nascent transcript exhibited a sedimentation coefficient of 35S, were less tightly associated to the template than their human counterparts, and displayed no detectable 3′-5′ exonuclease activity on the associated transcript. In contrast, blocked human elongation complexes were more tightly bound to the template, and multiple forms were identified, with the largest exhibiting a sedimentation coefficient of 60S. Analysis of the associated transcripts revealed that a subset of the human elongation complexes exhibited strong 3′-5′ exonuclease activity. Although isolated human preinitiation complexes were competent for efficient transcription, their ability to generate 60S elongation complexes was strikingly impaired. These findings demonstrate functional and size differences between S. cerevisiae and human RNAPII elongation complexes and support the view that the formation of mature elongation complexes involves recruitment of nuclear factors after the initiation of transcription.